Treatment of hepatic insufficiency with glucagon-insulin: Part I. Improvement of hepatic encephalopathy and changes of blood ammonia levels by glucagon-insulin treatment - KINOSHITA, Hiroshi; SHIRAI, Yuichi; SAITO, Michiko; FUJITA, Hideo; FUJISHIMA, Akira; SUGA, Mitsuo; ANZAI, Tetsuro; HOSOKAWA, Yukio; YOKOYAMA, Yoko (Kanzo, 1980)
The clinical effect of the treatment of hepatic encephalopathy with intravenous glucagon and insulin (G-I) was studied. Both of 2 cases with acute hepatic insufficiency survived, whereas the survival in chronic hepatic insufficiency was 2 out of 6 cases, so that the over-all survival rate was 50%. Improvement of the conciousness state, including temporary arousal, was observed in 7 of 8 cases, and the average period required before arousal was 4 days. The improvements of the consciousness states were accompanied by decreases of blood ammonia levels within 3 hours after the start of the infusion, whereas this could not be observed in cases where the G-I treatment was ineffective. Cases with acute hepatic insufficiency showed improvements of GOT and GPT levels, while no appreciable improvement was observed in chronic cases. It is concluded that the G-I treatment is a very effective method, at least no less effective than any of the conventional methods, of treatment for the control of hepatic insufficiency. The mechanism of action of this treatment was discussed.